Produksi Pesan Korporat Melalui Video Lebaran 1444 H PT Petrokimia Gresik - Setiawan, Ramzy Fauza; Dirgantara, Pradipta (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
In the digital era, companies are faced with the complexity of conveying corporate messages effectively. Digital communication, especially through video media, is a crucial strategy. This research analyzes the role of digital communication through a case study of PT Petrokimia Gresik's Eid 1444 H video. Analyze the effectiveness of the use of digital communications and its impact on audience perception and engagement. This research aims to provide an understanding of the significance of digital communication in disseminating corporate messages and strengthening audience engagement in the digital era. The conclusion shows that the production of corporate messages through creative videos opens up new opportunities for corporate interactions with audiences via social media, despite facing budget and time challenges.